Análise da despesa com pessoal do Poder Executivo do Estado do Ceará, à luz da Lei de Responsabilidade Fiscal - Aguiar, Antônio Linconl de Aguiar (2022)
This study aimed to demonstrate the behavior of the Executive Power of the State of Ceará regarding compliance with the limits on personnel expenses defined in the Fiscal Responsibility Law (LRF), in the period from 2010 to 2021. This is a exploratory, descriptive, bibliographic, and documentary research. Data were collected from the state of Ceará Fiscal Management Reports, available on the Transparency Portal. Data analysis was performed using content analysis. The results indicate that the Executive Power of the State of Ceará complied with the limits of personnel expenses, defined in the LRF, except for the alert limit, in 2015. This study can contribute to broadening the understanding of the importance of controlling personnel expenses for the balance of public accounts and, consequently, for responsible fiscal management.